Solar wind control of the terrestrial magnetotail as seen by STEREO. Issue 8 (20th August 2014) - Opitz, Andrea; Sauvaud, Jean‐Andre; Klassen, Andreas; Gomez‐Herrero, Raul; Bucik, Radoslav; Kistler, Lynn M.; Jacquey, Christian; Luhmann, Janet; Mason, Glenn; Kajdic, Primoz; Lavraud, Benoit
Abstract At the beginning of 2007 the twin STEREO spacecraft provided a unique opportunity to study the global solar wind control of the terrestrial magnetotail under typical solar activity minimum conditions. The STEREO‐B (STB) spacecraft flew in the vicinity of the far terrestrial magnetotail, while the STEREO‐A (STA) spacecraft was located in front of the Earth performing measurements in the undisturbed solar wind. In February, the STB spacecraft was located in the magnetosheath most of the time but experienced several incursions into the distant magnetotail. Comparison of STA and STB observations determines unambiguously whether solar wind events such as energetic particle enhancements observed by STB are of pure solar origin or due to the influence of the terrestrial magnetosphere. During this time period in 2007, there were solar minimum conditions with alternating fast and slow solar wind streams that formed corotating interaction regions, which were the dominating source of magnetospheric disturbances encountering the Earth almost every week. Under these conditions, STB experienced multiple bow shock and magnetopause crossings due to the induced highly dynamic behavior of the terrestrial magnetotail and detected bursts of tailward directed energetic ions in the range of 110–2200 keV accompanied by suprathermal electrons of 700–1500 eV, which were not seen in the undisturbed solar wind by STA. The corotating interaction regions triggered these energetic particle enhancements, and we demonstrate their magnetosphere‐related origin. Even after leaving the magnetosheath in March 2007, STB continued to observe antisunward directed energetic ion bursts until May up to a distance of 800 RE behind Earth, the largest distance to which solar wind and magnetospheric interaction has been observed. These results show that Earth is a very significant source of energetic particles in its local interplanetary environment.